STRENGTHENING HUMAN CAPITAL MANAGEMENT IN MSMEs TO IMPROVE BUSINESS PERFORMANCE AND SUSTAINABILITY - Chablullah Wibisono; Nolla Puspita Dewi; Nurhatisyah; Ely Kurniawati (RADJA PUBLIKA, 2025)
Strengthening human capital is Wrong One factor key in increase performance And sustainability of Micro , Small and Medium Enterprises Medium Enterprises (MSMEs). However , many MSMEs still face limitations in management source Power human impact​ on low productivity And Power competition business . Activities devotion to public This aim For increase human capital capacity in MSMEs through approach training And mentoring based empowerment . Method implementation use approach participatory which includes stage identification needs , training management source Power human , assistance implementation , as well as monitoring and evaluation . Results activity show existence improvement understanding partners to draft human capital management , improvement skills in management power work , and implementation practice simple HR management like distribution Work And preparation of SOPs. In addition that , there is indication improvement performance marked effort​ with increasing productivity And efficiency operational . Findings This in line with various studies that confirm that training And mentoring contribute significant to improvement human resource capacity and MSME performance In a way Overall , the human capital strengthening program through training And mentoring proven effective in push transformation management of MSME human resources from approach traditional going to better management​ strategic . Implications from activity This show that human capital development is not only increase performance business in term short , but Also strengthen sustainability of MSMEs in face dynamics environment business .